THE ROLE OF FABRICS AND DECORATIVE ELEMENTS IN TRADITIONAL UZBEK WOMEN’S CLOTHING - Ochilova Marjona O‘tkir qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the role of fabrics and decorative elements in traditional Uzbek women’s clothing. The study analyzes the use of fabrics such as atlas and adras, embroidery, gold-thread decorations, and patterns in enhancing the aesthetic and cultural value of garments. Modern technologies in garment production are also considered, highlighting how traditional elements are adapted in contemporary fashion.